Effect of Geogrid Layer on Sand and Clay Soil Deformation Under The Site Foundation - Nawawi, Yudith Surya Ambhita; Nurly Gofar (Universitas Negeri Semarang, 2025)
Two things must be evaluated when planning a shallow foundation: sufficient bearing capacity and non-excessive settlement. In theory, foundation-bearing capacity analysis is based on Terzaghi or Meyerhoff's theory. Terzaghi's theory assumes that the soil under the foundation is uniform to an infinite depth and has sufficient strength to withstand the applied load (Gofar & Kassim, 2007). In reality, the soil beneath the foundation does not always have adequate bearing capacity, which results in excessive settlement (Shahin et al., 2017). Soil replacement using good quality soil is commonly used to improve the bearing capacity of soft soils in a particular location. Many soil improvement methods have been used, including soil compaction, additives, hydraulic methods such as PVD installation, and inclusion methods. Another alternative is to install a layer of geotextile or geogrid under the foundation to increase bearing capacity and reduce deformation. Several studies on improving soil bearing capacity under footing foundations show a significant increase in bearing capacity due to installing geotextile or geogrid layers at a certain distance under the footing foundation. This research uses a numerical method where the analysis is carried out on a hypothetical model with a geometry comparison that matches the laboratory-scale model research conducted by Ambhita (2020). Numerical analysis was performed using SIGMA/W (Geoslope International, 2018). The results showed that the foundation settlement on the medium clay layer without geogrid reinforcement was more significant than on the sand layer with geogrid reinforcement. Using geogrid layers increases the stiffness of the soil so that the deformation (settlement) is more minor, and the placement pattern of the geogrid layer affects the deformation that occurs.